An investigation of microtubule-kinetochore attachment mechanisms - Murray, Lucas Edward (My University, 2024)
The ability to replicate is a defining feature of life. At the center of eukaryotic cell division are a set of protein machines responsible for pulling apart the chromosomes before cells divide. Spindle microtubules grow from the poles of the cell and connect to chromosomes via protein complexes called kinetochores. Kinetochores must maintain tenacious attachments to microtubule tips, even as they assemble and disassemble underneath their grip. Additionally, kinetochores mediate an error correction process to ensure the proper attachments to microtubules are formed before separation of the chromosomes commences. Here, I work to understand how the proteins in the kinetochore work together to maintain attachments to microtubules. I investigate two different mechanisms for microtubule-kinetochore attachment: the conformational wave mechanism and the biased diffusion mechanism. I developed a new optical trapping assay, using it to show that microtubule protofilament morphological and energetic properties can be measured and changed. I investigate the role of protofilament curl enlargement in the attachment and motility of the kinetochore. I develop theoretical models that show that the biased diffusion mechanism can fit experimentally measured detachment rates for assembling and disassembling kinetochores. Finally, I show kinetochores exhibit asymmetry in their sliding friction when they are dragged along microtubule lattices, a new phenomenon for microtubule-kinetochore biophysics. I argue this sliding friction forms the basis for a new mode of error correction during cell division, one that likely holds across most eukaryotic organisms.
Thesis (Ph.D.)--University of Washington, 2024
Keywords: Cell division; kinetochore; microtubule; mitosis; optical trap; protofilament; Biophysics; Physiology and biophysics